Bipolar porous polymeric frameworks for low-cost, high-power, long-life all-organic energy storage devices - Sakaushi, Ken; Hosono, Eiji; Nickerl, Georg; Zhou, Haoshen; Kaskel, Stefan; Eckert, Juergen (Journal of Power Sources, 2014)
Organic-based energy storage devices are of great interests due to their high potential as affordable, high-performance energy storage devices. Especially, all-organic energy storage devices, where cathode and anode are constituted of organic compounds, could be an extremely affordable device expected to be applied to smart grids. Recent reports on bipolar porous polymeric frameworks (BPPFs) suggest very promising features of this new organic electrode group towards high-performance energy storage devices. Here, we studied an all-organic system using BPPFs for both anode and cathode parts. The formation of BPPFs was confirmed by Raman spectroscopy and N2 isotherm measurements. The electrochemical properties of this all-organic energy storage device using BPPFs showed a high-power density of 1 kW kg-1 based on the total mass of the BPPFs and a long cycle life of over 1000 times. © 2013 Elsevier B.V. All rights reserved.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Affordability; All-organic batteries; High-power density; Long cycling life